The basis of Medicine: anatomy as a fundamental part of academic training and professional security (Research, Society and Development, 2022)
Introduction: Anatomy is the science that studies the structure of the human body and the integration of organic systems, requiring detailed anatomical knowledge to act in a clinical and surgical manner. However, in current medicine, there is a reduction in the workload dedicated to anatomy, as well as a change in teaching methodology, which caused a deficit in the teaching and learning of anatomy in educational institutions. Objective: To evaluate the teaching and learning of anatomy in the medical course. Methodology: Descriptive bibliographic review in an exploratory qualitative approach, based on scientific publications found in the PUBMED, SCIELO and Virtual Health Library databases. Results: The study had a sample of 8 articles, of which the need for study from cadavers was mentioned in all articles, the training of professionals was explained in 5 works, on methodologies of studies in higher institutions were mentioned in 5 scientific reviews. Discussion: It is observed that the anatomy in medical institutions has changed over time, with the reduction of workload, computerization of content and technological introduction. However, it is evident that in order to study and understand other disciplines in the academic curriculum, a deep anatomical knowledge is necessary. Conclusion: It is necessary to integrate the subjects so that there is a better clinical reasoning, which is not a reality in most faculties, since they are addressed separately between the semesters. In addition to the lack of corpses and trained professionals in some institutions.